Models for risk aggregation and sensitivity analysis: an application to bank economic capital - Jacobs, Michael (Henry Stewart Talks, 2012)
Value at Risk, The method of copulas, Data description, Call report variables, Call report and CRSP, Loss distributions, Time series, 5 risk types, Dependogram of multivariate tests, Diversification benefit, Copula goodness of fit (GOF), Bootstrap of margins & correlations